White spots around colorectal tumors are cancer-related findings and may aid endoscopic diagnosis: a prospective study in Japan - Kai Korekawa; Yusuke Shimoyama; Fumiyoshi Fujishima; Hiroshi Nagai; Takeo Naito; Rintaro Moroi; Hisashi Shiga; Yoichi Kakuta; Yoshitaka Kinouchi; Atsushi Masamune (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims During endoscopy, white spots (WS) are sometimes observed around benign or malignant colorectal tumors; however, few reports have investigated WS, and their significance remains unknown. Therefore, we investigated the significance of WS from clinical and pathological viewpoints and evaluated its usefulness in endoscopic diagnosis. Methods Clinical data of patients with lesions diagnosed as epithelial tumors from January 1, 2019, to December 31, 2020, were analyzed (n=3,869). We also performed a clinicopathological analysis of adenomas or carcinomas treated with endoscopic resection (n=759). Subsequently, detailed pathological observations of the WS were performed. Results The positivity rates for WS were 9.3% (3,869 lesions including advanced cancer and non-adenoma/carcinoma) and 25% (759 lesions limited to adenoma and early carcinoma). Analysis of 759 lesions showed that the WS-positive lesion group had a higher proportion of cancer cases and larger tumor diameters than the WS-negative group. Multiple logistic analysis revealed the following three statistically significant risk factors for carcinogenesis: positive WS, flat lesions, and tumor diameter ≥5 mm. Pathological analysis revealed that WS were macrophages that phagocytosed fat and mucus and were white primarily because of fat. Conclusions WS are cancer-related findings and can become a new criterion for endoscopic resection in the future.